THE ROLE OF SOCIO-CULTURAL REFORMS IN THE EDUCATION OF A WELL-ROUNDED GENERATION - Gularo Nishonbayeva (American Journals Publishing, 2025)
This article briefly describes the reforms being carried out today in the cultural and educational sphere, as well as measures aimed at raising the cultural level of young people.